2004
DOI: 10.1007/s00520-004-0641-2
|View full text |Cite
|
Sign up to set email alerts
|

Piperacillin-tazobactam and netilmicin as a safe and efficacious empirical treatment of febrile neutropenic children

Abstract: This study suggests that piperacillin-tazobactam in association with netilmicin presents a satisfactory efficacy and a good tolerance as empirical therapy for febrile neutropenic children. It allowed us to maintain the bacterial ecology of our unit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 20 publications
2
3
0
Order By: Relevance
“…Corapcioglu et al 9 and Uygun et al 22 demonstrated that PIP/TAZO monotherapy showed no inferiority to cefepime treatment in pediatric FN with cancer. The treatment success without modification in the PIP/TAZO group in our study of 59.6% was in agreement with other reports in which the study population consisted of both hematological malignancies and solid tumors 9, 22–24. The treatment success without modification for PIP/TAZO with or without aminoglycoside was 56% by Corapcioglu et al 9, 60% by Uygun et al 22, 77% by Le Guyader et al 23, and 42% by Aksoylar et al 24.…”
Section: Discussionsupporting
confidence: 91%
“…Corapcioglu et al 9 and Uygun et al 22 demonstrated that PIP/TAZO monotherapy showed no inferiority to cefepime treatment in pediatric FN with cancer. The treatment success without modification in the PIP/TAZO group in our study of 59.6% was in agreement with other reports in which the study population consisted of both hematological malignancies and solid tumors 9, 22–24. The treatment success without modification for PIP/TAZO with or without aminoglycoside was 56% by Corapcioglu et al 9, 60% by Uygun et al 22, 77% by Le Guyader et al 23, and 42% by Aksoylar et al 24.…”
Section: Discussionsupporting
confidence: 91%
“…PIPC/ TAZ monotherapy was reported not to be inferior to CFPM monotherapy in pediatric patients with FN [8,9]. In our study, the overall treatment success rate without modifications in the TAZ/ PIPC group was 62.1%, which was consistent with the findings of previous studies [8][9][10][11][12]. We examined several other parameters, including success rates in patients with absolute neutrophil counts less than 0.5 Â 10 9 /l at the end of the treatment, the rate of new infections, success rates in patients with bacteremia, and mortality, in order to compare the effectiveness of the two drugs; however, no differences were observed in these parameters.…”
Section: Discussionsupporting
confidence: 92%
“…Some combination regimens include cefepime plus amikacin [23,24], piperacillin-tazobactam plus netilmicin [25,26], and meropenem plus amikacin [25] combinations.…”
mentioning
confidence: 99%